(untitled) (Research, Society and Development, 2023)
The diagnosis of periodontal disease is made through a clinical examination (periodontal probing), aided by imaging exams and the patient’s past medical history. Once diagnosed, periodontitis is classified according to its severity, and a treatment plan is developed with the aim of removing the biofilm, which is a triggering factor for the disease. In stages III and IV of periodontitis, antibiotics are often chosen as adjuncts to mechanical therapy. Among the standard drugs, the combination of metronidazole and amoxicillin has been widely used, as these drugs together enhance their selective microbial action. Therefore, the goal of this review is to raise awareness within the dental community about the importance of chemotherapy in the treatment of periodontitis.